PERANCANGAN TINGKAT KEPUASAN MASYARAKAT TERHADAP KINERJA DPRD KOTA MEDAN MENGGUNAKAN PHP MYSQL - Lubis, Akbar Maulana; Zaidan, Muhammad; Hasugian, Abdul Halim (Universitas Ma Chung, 2025)
The development of technology in this modern era is a challenge for the government and encourages efforts to realize optimal services for the community. In carrying out its functions, the Medan City DPRD needs to know the extent of the public satisfaction index on the performance that has been built. Collecting a lot of data requires an information system in its implementation, and this is the purpose of this research. The design of this Information System was built by utilizing PHP technology and MySQL as the database. The development method used to produce a good system is using the SDLC development method with a waterfall model. The design is also arranged with an object-oriented analysis approach using UML (Unified Modeling Language). This system is designed to provide convenience in data processing and produce accurate and fast reports. By building a web-based community satisfaction index information system design, the Medan City DPRD government is expected to easily know the evaluation of the community satisfaction index, especially related to the services they provide, so that it becomes the basis for continuous improvement.